Representasi Perempuan Dalam Iklan Rokok - Arina Rahmatika (Institut Agama Islam Negeri Kendari, 2020)
AbstracCigarette advertisement is one of the ads that has an interesting concept because it is limited by some laws. So inevitably, demand that cigarette’s advertisement thinks harder in their efforts to display a cigarette without displaying the shape and embodiment of its product. So, don’t be surprised if cigarette advertisement can cause many interpretations and even cause contradiction in society. This case of cigarette advertisement A MILD Edition “Mula Mula Malu-Malu, Lama Lama Mau”. Based on the results of research by using analysis of Roland Barthes, then cigarette advertising shows that the advertisement does not apply of the principle of gender equality and woman’s emancipation, even advertising tend to be patriarchy, bend and change the image of woman in accordance with the product offered. Keyword: Advertisement, cigarette, woman